(3LQGFe JRjja GdYedI (B:s (3OQGSI ebGQfI (B/ s - (3YGOd MGaX ZGfes; (3eMehO eMehO eUWais; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1966)
(3JfbSe gPg GdQSGdI Edi KdGKI CbSGe, MjK jJfGhd GdbSe GdChd JLQje GdJRjja, hjJfGhd GdbSe GdKGfj CQcGf GdJRjja, hCNjQG jJfGhd GdbSe GdKGdK GdYbhHI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1966. s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI UaMGJ (B395 - 408.s
Keywords: (3GdbGfhf GdLfGFjs; (3JRjja GdYedIs; (3JLQje GdJRjjas; (3GdMeGjI GdLfGFjI GdYGdejI ddYedIs; (3GdJLQjje GdhbGFjs; (3GdYedI eMd GdLQjeIs; (3YdGbI GdJQhjL HGdJRjja s; (3GdCYPGQ GdeYajI ef GdYbhHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs